A Study of Internet Usage Differences Between Arab and Non-Arab Students : A Case Study of UUM's Postgraduate Students - Saifan, Abdultef Ali (2009)
This study is meant to be an exploratory study which intends to point out whether there is any difference between the usage of internet among Arab and Non-Arab students, Moreover, it intends to investigate the possible similarities of internet usage purpose, as well as to find out whether there is need Universiti Utara Malaysia to improve the ability of internet usage of postgraduate students of UUM. This study is conducted among postgraduate students who are registered at Universiti Utara Malaysia regardless of the students’ educational background, current field of study or social class position as long as they are taking postgraduate studies. The study found that the popularity of internet as major source of information is adequately higher than its written counterpart. The internet as research tool can be competitor of printed academic sources, which indicates that the written academic sources need promotion and protection from universities. The study also found that there are differences in the usage of internet among Arab and Non-Arab postgraduate students, but at the same time, it is shown that there are similarities in the usage of internet as well. In conclusion, suggestion was made to improvise the level of internet usage among Arab and non-Arab students.